Borderlands: traversing spaces between art making and research. (9th November 2015) - MacDonald, Abbey; Moss, Timothy
Abstract : Purpose: – The purpose of this paper is to offer a picture of the relationship the researchers perceive between the art and research practices, unravelling the ways the authors shape and inform enactment of a purposeful nexus between art making and research. Design/methodology/approach: – A hybridised methodology is adopted, where methods integral to narrative inquiry and a/r/tography are drawn together to generate a series of "pictures" of the interplay between research and artistry. Through exploration of critical events, creative prose and artefacts, the paper unfolds the parallels perceived and tensions encountered between the approaches to making art and conducting research. Findings: – Borders can create a sense of calm and safety in allowing us to organise and contain information or matter, but they are also provocative in their potential to be crossed. Through this work, the authors chart the borders of the art making and research, and how, why and when these borders might be traversed to augment the integrity of both practices. In unfolding and examining the experiences and the perceptions thereof, the authors articulate ways in which the authors find arts practice to enrich and inhibit the research, and vice versa. Originality/value: – Of particular value in this paper is the way in which the authors not only tell of the experiences as artists and researchers, but also show these experiences through a/r/tographic methods. As such this paper presents an approach to research that is generative, suggesting rather than concluding and challenging rather than resolving, and ultimately offering multiple avenues for artistic and analytic insight.